Worlds apart trading together : the organisation of long-distance trade between Rome and India in antiquity - Grønlund Evers, Kasper (Archaeopress Roman archaeology ;, 2017)
This text sets out to replace the outdated notion of 'Indo-Roman trade', integrating new findings from the last 30 years. Analysis conducted demonstrates that highly substantial levels of trade took place between the Mediterranean and the Indian Ocean in the 1st-6th c. altering consumption and production in India, South Arabia, and the Roman Empire.